Anatomic morphology and clinical significance of intraforaminal ligaments of the cervical spine. Issue 5 (19th March 2019) - Yang, Yemei; Shi, Benchao; Duan, Yang; Qiu, Sujun; Liu, Zhenhua
Abstract : The cause of cervical spondylotic radiculopathy could be related to the intraforaminal ligaments (IFLs) of the cervical spine. The aim of this study is to identify and describe the IFLs and assess their clinical significance. Six intact cervical spine specimens from adult embalmed cadavers were dissected to expose the cervical nerve roots and their surrounding intraforaminal tissues fully. From the C1‐C2 to the C7‐T1 intervertebral foramina (IVF), the connective structures between each nerve root and its surrounding foraminal wall were examined under a surgical microscope. The morphology, number, and attachment points of the IFLs of each segment were documented, and the length, width, or diameter and thickness of the ligaments were measured with a vernier caliper. IFLs were observed in all 84 IVFs of the cervical spine. According to their locations, they can be divided into two categories: the first is entrance‐zone IFLs, which are radially distributed around the nerve root; the second is mid‐zone IFLs, which are thin, strip‐shaped fibrous tissues intertwined around the nerve roots, the number of ligaments being considerable but difficult to quantify. Ligament structures have been identified in the IVF of the cervical spine. Under physiological conditions, they could be protective in maintaining the position, shape, and function of nerve roots. However, under pathological conditions, the IFLs of the cervical spine could aggravate the symptoms of cervical nerve root radicular pain associated with other types of compression. Clin. Anat. 32:654–660, 2019. © 2019 Wiley Periodicals, Inc.